The Effect of Duty Patterns on Circadian Rhythm among Air Traffic Controllers at Jakarta Air Traffic Service Centre - Mohamad Galih Adipradana; Emilia Rahajeng Larasati; Dhian Supardam (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Jakarta Air Traffic Service Centre (JATSC), Indonesia’s busiest air navigation facility, operates a 24-hour rotating duty system that potentially disrupts air traffic controllers’ (ATC) circadian rhythms. Such disruptions, particularly from night shifts, are associated with impaired sleep quality, increased fatigue, and decreased cognitive performance, which may affect flight safety. This study aims to analyze the effect of shift patterns on the circadian rhythm of ATCs at JATSC by comparing differences in sleep quality and fatigue levels among morning, afternoon, and night shift groups. The research employed a quantitative approach with a comparative descriptive survey design. Data were collected using demographic questionnaires, the Pittsburgh Sleep Quality Index (PSQI), and the Fatigue Severity Scale (FSS) from 82 actively licensed ATCs selected through stratified random sampling. Results revealed that all respondents experienced poor sleep quality (mean PSQI = 9.22), while night shift controllers showed the highest fatigue scores (mean FSS = 5.13). Statistical analysis using one-way ANOVA confirmed significant differences in both sleep quality and fatigue among shift groups. The findings emphasize that irregular duty rotations negatively affect physiological recovery and alertness, highlighting the need for fatigue risk management and duty scheduling aligned with circadian principles to maintain operational safety at JATSC.